Hormonal correlates of male life history stages in wild white-faced capuchin monkeys (Cebus capucinus) - Jack, Katharine M. (2013)
Much attention has been paid to hormonal variation in relation to male dominance status and reproductive seasonality, but we know relatively little about how hormones vary across life history stages. Here we examine fecal testosterone (fT), dihydrotestosterone (fDHT), and glucocorticoid (fGC) profiles across male life history stages in wild white-faced capuchins (Cebus capucinus). Study subjects included 37 males residing in three habituated social groups in the Área de Conservacíon Guanacaste, Costa Rica. Male life history stages included infant (0 to <12 months; N = 3), early juvenile (1 to <3 years; N = 10), late juvenile (3 to <6 years; N = 9), subadult (6 to <10 years; N = 8), subordinate adult (≥10 years; N = 3), and alpha adult (≥ 10 years; N = 4, including one recently deposed alpha). Life history stage was a significant predictor of fT; levels were low throughout the infant and juvenile phases, doubled in subadult and subordinate adults, and were highest for alpha males. Life history stage was not a significant predictor of fDHT, fDHT:fT, or fGC levels. Puberty in white-faced capuchins appears to begin in earnest during the subadult male phase, indicated by the first significant rise in fT. Given their high fT levels and exaggerated secondary sexual characteristics, we argue that alpha adult males represent a distinctive life history stage not experienced by all male capuchins. This study is the first to physiologically validate observable male life history stages using patterns of hormone excretion in wild Neotropical primates, with evidence for a strong association between fT levels and life history stage.